2019
DOI: 10.1071/mf18423
|View full text |Cite
|
Sign up to set email alerts
|

Element composition of shark vertebrae shows promise as a natural tag

Abstract: Reconstructing movements and environmental histories of sharks may be possible by using the element composition of vertebrae, but unlocking such possibilities requires an understanding of the effects of extrinsic and intrinsic factors on element composition. We assessed water temperature and pH effects (independently and in combination) on vertebral chemistry of Port Jackson sharks while accounting for intrinsic factors (condition and sex) using indoor aquaria and outdoor mesocosm environments, where the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Excluded were studies (or individual responses) that (i) lacked a suitable control treatment, TABLE 1 | Summary of the references including in the analysis across the different treatments, namely experimental warming (EW), acidification (EA), deoxygenation (ED), and their combination (EWA and EWD). Neale et al, 1977;Du Preez et al, 1988;Fangue and Bennett, 2003;Tullis and Baillie, 2005;Mull et al, 2008;Rodda and Seymour, 2008;Dabruzzi et al, 2013;Rosa et al, 2014Rosa et al, , 2016aDi Santo, 2015, 2016Pistevos et al, 2015;Johnson et al, 2016;Whitney et al, 2016;Lear et al, 2017;Pistevos et al, 2017Pistevos et al, , 2019Luongo and Lowe, 2018;Pouca et al, 2018Pouca et al, , 2019Di Santo, 2019;Hume, 2019;Schwieterman et al, 2019;Bouyoucos et al, 2020a,c;Crear et al, 2020;Musa et al, 2020;Pegado et al, 2020b;Gervais et al, 2021;Wheeler et al, 2021 EA Green andJutfelt, 2014;Heinrich et al, 2014Heinrich et al, , 2016Rosa et al, 2014Rosa et al, , 2016aDi Santo, 2015, 2016Dixson et al, 2015;Pistevos et al, 2015Pistevos et al, , 2017…”
Section: Literature Searchmentioning
confidence: 99%
“…Excluded were studies (or individual responses) that (i) lacked a suitable control treatment, TABLE 1 | Summary of the references including in the analysis across the different treatments, namely experimental warming (EW), acidification (EA), deoxygenation (ED), and their combination (EWA and EWD). Neale et al, 1977;Du Preez et al, 1988;Fangue and Bennett, 2003;Tullis and Baillie, 2005;Mull et al, 2008;Rodda and Seymour, 2008;Dabruzzi et al, 2013;Rosa et al, 2014Rosa et al, , 2016aDi Santo, 2015, 2016Pistevos et al, 2015;Johnson et al, 2016;Whitney et al, 2016;Lear et al, 2017;Pistevos et al, 2017Pistevos et al, , 2019Luongo and Lowe, 2018;Pouca et al, 2018Pouca et al, , 2019Di Santo, 2019;Hume, 2019;Schwieterman et al, 2019;Bouyoucos et al, 2020a,c;Crear et al, 2020;Musa et al, 2020;Pegado et al, 2020b;Gervais et al, 2021;Wheeler et al, 2021 EA Green andJutfelt, 2014;Heinrich et al, 2014Heinrich et al, , 2016Rosa et al, 2014Rosa et al, , 2016aDi Santo, 2015, 2016Dixson et al, 2015;Pistevos et al, 2015Pistevos et al, , 2017…”
Section: Literature Searchmentioning
confidence: 99%
“…The potential impact of hypercapnia on mineralisation in elasmobranchs has been less studied so far: Chronic hypercapnia has an impact on the skeleton of juvenile (i.e. developing) skates 31 and a minor effect on mineralisation of vertebrae of juvenile sharks 32 . When the impact of hypercapnia on chondrichthyan denticles was investigated, no effects were found in juvenile catshark 21 (4–6 months at 1100 µatm) and skate embryos 31 (1 month at 990 µatm).…”
Section: Introductionmentioning
confidence: 99%
“…The Mg/Ca ratio has been called the ‘chemical clock’ in some fish species due to its association with seasonal growth rates, and one controlled elasmobranch study has found limited evidence that Mg incorporation increases with condition (Limburg et al, 2018; Pistevos et al, 2019). Without additional information about sawfish in particular it is impossible to determine, but the repeated sharp peaks in this tracer are suggestive of periods of higher and lower growth (figure 3D), a relationship which merits further study.…”
Section: Discussionmentioning
confidence: 99%